Relations between communist and third world countries - Henrik Bischof (Intereconomics, 1976)
Despite the unproportionately low level of Soviet economic assistance, Soviet influence in the Third World is quite considerable at present. Taking this fact as a starting point the following article examines the principles guiding relations between communist and developing countries.
Keywords: 330; East-South Relations